(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione – 2. Le mutilazioni genitali femminili come atto di violenza nelle norme e nei documenti europei degli anni 2000 – 3. Escissione e abuso/brutalità/violenza: binomi appropriati e inevitabili? – 4. L’escissione, il dolore e la sua reinterpretazione – 5. Il rapporto dell’escissione con la comunità, la famiglia e il matrimonio – 6. La Convenzione di Istanbul, le norme francesi e i rischi per la libertà religiosa – 7. Considerazioni conclusive. Female Genital Mutilation as a Gender-Based Crime? (An Analysis of the European Norms in Light of the Concepts of Violence and Religious Freedom) ABSTRACT: Female genital mutilations (FGM) are ancient practices, which are widespread in several geographical areas, and particularly in Africa. The conflict between customary norms and state legal systems, which arises because FGM violate fundamental rights like the right to physical integrity, health, and non-discrimination based on gender/ethnicity/culture, discloses the dialectic between two normative universes; these universes are conceptually distant with regard to the priority given to the individual and the group. Focusing on the reasons related to female genital cutting (FGC), which consists of the ablation, to differing degrees, of female genital organs, this article, argues that the link that European norms establish between FGM and violence, abuse or brutality comes into conflict with the reasons why migrants perpetuate FGC. Therefore, the way gender is mainstreamed into European norms on FGM can have negative effects, which concern courts’ implementation of these norms and migrants’ social inclusion. Furthermore, this article claims that focusing on health instead of gender equality may prove more effective for the eradication of FGM. Through an analysis of French law, it also suggests that the way the national law is adapted to conform to the Istanbul Convention, may represent a danger to religious freedom.